Interwoven: Culture, language, and learning strategies - Oxford, Rebecca L.; Gkonou, Christina (Studies in Second Language Learning and Teaching, 2018)
Culture, language, and learning strategies form a grand tapestry, which is this article’s theme. The authors explain each part of the tapestry, provide ideas for teaching all parts in a smoothly united way, and explore key cultural issues (i.e., cognitive flexibility, ethnocultural empathy, intercultural understanding, and needs of intercultural trauma survivors). The article discusses cultural types, cultural communication styles, and related strategies, and it identifies publications that draw together culture, language, and strategies. The article offers new insights and abundant examples for teachers, teacher educators, and researchers.